Histogram Equalization with Filtering Techniques for Enhancement of Low Quality Microscopic Blood Smear Images - Oussama, Laghouiter; Abdul Jamil, Muhammad Mahadi; Hafizah, Wan Mahani; Adon, Mohamad Nazib (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents image enhancement and filtering techniques for microscope blood smear image, in order to improve low image quality that have characteristics: blurred, the diminished true color of objects which are cells , unclear boundary and low contrast between the cells and background. Therefore in this paper proposed histogram equalization (HE) technique followed with filtering techniques such as median filter. HE utilizing to adjust the contrast which based on intensity pixels values, hence able to measure image quality through image histogram as shown in results, while removing noise from the images using filtering and gamma correction parameter in order to distinguish between background and foreground (cells) to get clear borders also. These techniques have been implemented on 46 blood samples. The proposed method successfully improve the readability of the cells in the low quality of blood smear images this mean that contain more information with a good effectiveness which lead for the correct sickness detection and data analysis.